Comparative Analysis of Shale Gas Enrichment and High Yield Geological Conditions of Wufeng–Longmaxi Formation and Qiongzhusi Formation in Southern Sichuan Basin - Majia Zheng; Hui Long; Ya Wu; Zhipeng Ou; Wenlei Liu; Dandan Wang; Wenyi Chen; Zhenxue Jiang; Xianglu Tang (Geofluids)
Wufeng–Longmaxi Formation and Qiongzhusi Formation are the significant shale gas exploration strata in China. The former has made a major breakthrough, and the exploration of the latter is restricted. At present, it shows good exploration potential in the Qiongzhusi Formation. Based on the field outcrop and core logging data, the production data from drilled shale gas wells and previous research results combined with the determination of organic matter content, laser Raman spectroscopy of organic matter, X-ray diffraction experiments, and field emission scanning electron microscopy observations. This study compares the geological conditions and control factors of shale gas enrichment and high yield in the Wufeng–Longmaxi Formation and Qiongzhusi Formation and clarifies the enrichment mode of two sets of shale gas reservoirs. The results show that the organic geochemical conditions of two sets of shale reservoirs are similar, about 0.5%~4.5%. The quartz content of Wufeng–Longmaxi Formation shale (42.5%) is more than that of Qiongzhusi Formation (34.1%~40.2%), and the feldspar content (6.4%) is less than that of Qiongzhusi Formation (20.5~27.3%). The inorganic pores of the Qiongzhusi Formation are more developed than those of the Wufeng–Longmaxi Formation, and the pore size of inorganic pores can reach 100 nm~1 μm. Both of them have good preservation conditions. The enrichment of shale gas in the Wufeng–Longmaxi Formation is controlled by hydrocarbon generation reservoir-preservation conditions, and the enrichment of shale gas in the Qiongzhusi Formation is mainly controlled by geological structure. It is of great significance to clarify the enrichment control factors of the Qiongzhusi Formation for effectively guiding the continuous exploration and development of the Qiongzhusi Formation. Shale gas exploration in the Qiongzhusi Formation has a very large prospect, which is expected to exceed the Longmaxi Formation.